Workers’ Perceptions of Earnings Growth and Employment Risk - Koşar, Gizem; van der Klaauw, Wilbert (Journal of Labor Economics, 2025)
In addition to realized earnings and employment shocks, forward-looking individuals are presumed to condition their consumption and labor supply decisions on their subjective beliefs about future labor market risks. This paper uses rich panel data to document considerable individual heterogeneity in earnings growth expectations and in the perceived likelihood of voluntary and involuntary job exits. We examine how expectations evolve over the working life and business cycle and how they covary with macroeconomic expectations and personal experiences. While largely consistent with patterns in realized outcomes, our findings highlight the unanticipated nature of the pandemic recession and the ensuing resignation wave.